Toni Rüttimann and His Bridge Building Approach. Issue 1 (2nd January 2020) - Alatalo, Erika
Abstract: Toni Rüttimann has been building bridges together with local partners and rural communities in Latin America and Southeast Asia since 1987. He has no engineering degree, no company or NGO, does no fundraising, and receives no salary—and yet he has built more than 800 suspension bridges. Over the years he has developed an efficient system where local people, international companies, generous friends and local governments all play a role. The key is working together with the locals, having the local villagers build their own bridges and utilizing the fact that bridges serve a lot of people. Another important part of Toni's approach is using whatever resources and materials are available. The paper is largely based on discussions with Toni and a field visit to two bridge sites and the welding yard in Myanmar in April 2019 as well as a private communication with Toni via e-mail.